English, asked by piyushgarg7719, 8 months ago

(cosec A + sin A) (cosec A - sin A) = cot² A + cos² A,​

Answers

Answered by sairamghuge8808
0

Answer:

solve with your mind ask in online class

Answered by anantya30
1

answer

(sinA+cscA)

2

+(cosA+secA)

2

=sin

2

A+csc

2

A+2sinAcscA+cos

2

A+sec

2

A+2cosAsecA .......As[a²+b²+2ab=(a+b)²]

=sin

2

A+csc

2

A+2sinA×

sinA

1

+cos

2

A+sec

2

A+2cosA

cosA

1

.

........... since secA=

cosA

1

and cscA=

sinA

1

=sin

2

A+csc

2

A+2+cos

2

A+sec

2

A+2

=(sin

2

A+cos

2

A)+csc

2

A+sec

2

A+4

=1+1+cot

2

A+1+tan

2

A+4 ........... since csc

2

A=1+cot

2

A and sec

2

A=1+tan

2

A

=7+tan

2

A+cot

2

A

Hence proved

please inbox me and mark me as brainliest ✨

Similar questions